BUDAYA SIRIQ DI SULAWESI SELATAN DALAM NOVEL PULAU KARYA ASPAR SUATU TINJAUAN STRUKTURAL GENETIK - St. Nursa’adah (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This research have purpose to  explaining about  siriq’ s culture that is figured in  novel Island and  explaining  relevance between author background with cultural siriq  that  available in  novel. This Analisis used review of genetic structuralism. Method that used is qualitative descriptive method, method that emphasize to result through interpretation. The result of observation is showed to that structure of novel Pulau having homology’s relationship with opinion social world of authors. Structure Pulau created by author as an expression as view world of author to siriq’s culture of south sulawesi to responds of problem siriq at south Sulawesi. Changing concept of this siriq as  structuralism and modification of author in terms globalization influence. The world views expects to balance among siriq values with humanitarianism value which rational, morality, and responsibility.